Indigenous Knowledge: Implications in Tribal Health and Disease - K.E. Raj Pramukh and P.D.S. Palkumar (Stud. Tribes Tribals, 4(1): 1-6 (2006), 2006)
Indigenous knowledge research is a recent trend in the sociological and anthropological domains. Hither to fore, all developmental programmes initiated especially by the Government agencies have adopted a top-down approach, i.e., planning, distribution, and resources in-flow and perceptions flow from top to down. This trend has been recently reversed with a growing realization that for any successful implementation of planned programme, people's participation becomes imperative. In this context, participatory research techniques have been generated in different social sciences. The main thrust in such an approach is to make the people or the subjects into active collaborators in bringing about desired change. In this background research on Indigenous knowledge systems is growing steadily and anthropological contributions in this area have been greatly acknowledged, as the basic research methodology adopted by Anthropologists is participant observation method. In fact, the pioneers in documenting indigenous knowledge systems all over the world, especially among the less advanced, disadvantaged tribal and rural masses were none other than the Anthropologists. In the area of health and disease too, many anthropologists have undertaken documentation of health-related issues. Nonetheless, explanations offered in this domain are mostly divinatory in nature implying the divine wrath as causative of all diseases. In this paper, an attempt is made toillustrate the health status of the Tribals of Eastern Ghats and their health seeking behaviour and beliefs. Despite the fact that tribal societies exhibit similarities in many aspects related to health and disease, local variations persist.